Pulmonary complications of predominantly antibody immunodeficiencies in a tertiary lung center - Mahdaviani, Seyed Alireza (Interv Med Appl Sci, 2018)
BACKGROUND AND AIMS: Respiratory infections are expressed very soon in the life in humoral immunodeficiencies and often lead to chronic irreversible complications such as bronchiectasis and chronic airflow limitation. This study was conducted to evaluate the pulmonary complications of predominantly antibody immunodeficiencies to show the benefits of timely diagnosis and appropriate therapy. PATIENTS AND METHODS: The information of 48 patients involved with a type of predominantly antibody immunodeficiencies, including sex, type of primary immunodeficiency, age at the onset of symptoms, age at diagnosis, recurrent infections, respiratory symptoms, and pulmonary radiological and functional abnormalities were recorded and analyzed. RESULTS: In 48 patients evaluated, the mean age at diagnosis was 25.63 years. The mean diagnostic delay was estimated to be 13.62 years. The most recurring clinical manifestations, sinusitis (69.6%), otitis (43.5%), and recurrent pneumonia were the cause of frequent admissions in 68.8% of these patients. Bronchiectasis was frequently found (58.3%) in these patients mostly involving the middle and lower lobes (48.8% and 41.5%, respectively). CONCLUSIONS: Respiratory complications, infectious or non-infectious, determine the prognosis of the disease in patients with predominantly antibody immunodeficiencies. Timely diagnosis and appropriate management may improve life expectancy and the quality of life in these patients.